AB0308 Disease activity, grip strengths and hand dexterity in patients with rheumatoid arthritis. (15th June 2017) - Palamar, D; Er, G; Terlemez, R; Isil, U; Can, G; Saridogan, M
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease affecting hand joints, and leading impairment in hand functions. To date many scientific studies assessed the disease activity of patients with RA, but little attention has been carried out to assess hand functions, and dexterity (1–2). Objectives: The purpose of this study was to determine the clinical relevance of the Quick Disabilities of Arm, Shoulder and Hand (QuickDASH), hand dexterity with the Purdue Pegboard Test (PPT), and grip and pinch strengths of RA patients. Methods: Eighty-two women with a diagnosis of RA according to the 2010 American College of Rheumatology/the European League Against Rheumatism (ACR/EULAR) criterion were recruited to the study. The disease activity scores were determined by using Disease activity score-28 (DAS-28). Grip strengths was measured with a Jamar dynamometer, and pinch strengths were measured by pinchmeter. Hand functions were evaluated with the PPT, and functional outcomes were assessed with the QuickDASH questionnaire. Results: The mean age of the study group was 49.27±10.69 years. Average values of DAS-28, the QuickDASH values were found to be 4.22±1.28, 38.33±19.78, consecutively. High correlation was observed between DAS-28 and the QuickDASH values (p<0.001). The mean grip strengths were significantly correlated with the QuickDASH and DAS-28 values (p<0.01) (Table 1 ). The mean lateral pinch strengths were correlated significantly with DAS-28 and the QuickDASH scores (p<0.001). DAS-28 was correlated with PPT performance just on the dominant hand (p<0.05). The QuickDASH values were not correlated with all PPT performances (p>0.05). Grip strengths were positively correlated with the PPT performances (p<0.05). Conclusions: In conclusion, we determined that grip strengths were significantly related to disability and disease activity in RA patients in our study. The clinical significance of QuickDASH is high, and the questionnaire can be used effectively. References: Aktekin LA, Eser F, Baskan BM, et al. Disability of Arm Shoulder and Hand Questionnaire in rheumatoid arthritis patients: relationship with disease activity, HAQ, SF-36. Rheumatol Int.2011;31:823–6. Singh H, Kumar S, Talapatra P, et al. Assessment of hand functions in rheumatoid arthritis using SF-SACRAH (short form score for the assessment and quantification of chronic rheumatoid affections of the hands) and its correlation to disease activity. Rheumatol Int. 2012;32:3413–9. Disclosure of Interest: None declared